2019
DOI: 10.1017/s1092852919001688
|View full text |Cite
|
Sign up to set email alerts
|

Are serum brain-derived neurotrophic factor concentrations related to brain structure and psychopathology in late childhood and early adolescence?

Abstract: Objective. Mental disorders can have a major impact on brain development. Peripheral blood concentrations of brain-derived neurotrophic factor (BDNF) are lower in adult psychiatric disorders. Serum BDNF concentrations and BDNF genotype have been associated with cortical maturation in children and adolescents. In 2 large independent samples, this study tests associations between serum BDNF concentrations, brain structure, and psychopathology, and the effects of BDNF genotype on BDNF serum concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Prior literature investigating the association between circulating neurotrophic factors and brain structure, and specifically hippocampal volume, in youths remains scant. De Araujo et al 16 reported a null association of peripheral serum BDNF concentrations with subcortical volumes (i.e., left and right amygdala and hippocampus) and cortical thickness in children and adolescents. Likewise, in another study carried out in children and adolescents with bipolar disorder, peripheral serum BDNF levels were not correlated with either left, right or total hippocampal volumes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior literature investigating the association between circulating neurotrophic factors and brain structure, and specifically hippocampal volume, in youths remains scant. De Araujo et al 16 reported a null association of peripheral serum BDNF concentrations with subcortical volumes (i.e., left and right amygdala and hippocampus) and cortical thickness in children and adolescents. Likewise, in another study carried out in children and adolescents with bipolar disorder, peripheral serum BDNF levels were not correlated with either left, right or total hippocampal volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature investigating the association between circulating neurotrophic factors and brain structure, and specifically hippocampal volume, in youths remains scant. De Araujo et al (2019) reported a null association of peripheral serum BDNF concentrations with subcortical volumes (i.e. left and right amygdala and hippocampus) and cortical thickness in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations